Combination of Oligofructose and Metformin Alters the Gut Microbiota and Improves Metabolic Profiles, Contributing to the Potentiated Therapeutic Effects on Diet-Induced Obese Animals - Li, Qingzhong; He, Rui; Zhang, Fengmei; Zhang, Jian; Lian, Shihai; Liu, Hongxia (Frontiers in Endocrinology, 2020)
Accumulating studies implicate that the metformin (MET) and oligofructose (OFS) altered gut microbiota may play roles in the improvement of type 2 diabetes mellitus (T2DM) and obesity. However, whether the combined administration of OFS and MET could effectively affect the gut microbiota and improve metabolic profiles remains unknown. Here, we randomized diet-induced obesity (DIO) rats to OFS, MET or MET+OFS for 8 weeks and demonstrated that the combined administration of OFS+MET possessed potentiated effects on the glycemia , body weight and gut microbiome . In addition, fecal samples from MET and MET+OFS group were exchanged and transferred to germ free rats induced by antibiotics. Not surprisingly, the glucose tolerance and serum levels of endotoxin, FFA, TNF-α, IL-2, IL-6 were all sustainably improved among OFS+MET fecal microbia treated DIO rats while the MET fecal microbia treated ones presented a relatively reverse trend. Furthermore, transfer of fecal samples from the rats after 8 weeks treatment to antibiotics-treated germ-free mice significantly improved metabolic profiles, including glucose tolerance and weight reduction in mice that received MET+OFS-altered microbiota. In conclusion, the present study illustrated that the effects of OFS and MET combined treatment on gut microbiota, especially for the MET induced side-effects related ones, and host metabolism was of greater magnitude than individual OFS or MET treatment in obese rats and mice. Therefore, it is likely that combined administration of OFS and MET may offer a novel and promising strategy for reducding side-effects induced by MET and improving metabolic outcomes, particularly glycemia control and weight reduction.